Effects of thalamic deep brain stimulation on spontaneous language production. (August 2016) - Ehlen, Felicitas; Vonberg, Isabelle; Kühn, Andrea A.; Klostermann, Fabian
Abstract: The thalamus is thought to contribute to language-related processing, but specifications of this notion remain vague. An assessment of potential effects of thalamic deep brain stimulation (DBS) on spontaneous language may help to delineate respective functions. For this purpose, we analyzed spontaneous language samples from thirteen (six female / seven male) patients with essential tremor treated with DBS of the thalamic ventral intermediate nucleus (VIM) in their respective ON vs. OFF conditions. Samples were obtained from semi-structured interviews and examined on multidimensional linguistic levels. In the VIM-DBS ON condition, participants used a significantly higher proportion of paratactic as opposed to hypotactic sentence structures. This increase correlated negatively with the change in the more global cognitive score, which in itself did not change significantly. In conclusion, VIM-DBS appears to induce the use of a simplified syntactic structure. The findings are discussed in relation to concepts of thalamic roles in language-related cognitive behavior. Highlights: Particular language functions of the thalamus remain vague. We thus studied effects of thalamic deep brain stimulation on natural language. Stimulation did not impact on lexicality, stylistic devices, or errors. However, it did decrease sentence complexity. This effect suggests a thalamic role for syntactic language integration.